Comparison of eating quality and physicochemical properties between Japanese and Chinese rice cultivars. Issue 12 (1st December 2016) - Nakamura, Sumiko; Cui, Jing; Zhang, Xin; Yang, Fan; Xu, Ximing; Sheng, Hua; Ohtsubo, Ken'ichi
Abstract: In this study, we evaluated 16 Japanese and Chinese rice cultivars in terms of their main chemical components, iodine absorption curve, apparent amylose content (AAC), pasting property, resistant starch content, physical properties, sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis, and enzyme activity. Based on these quality evaluations, we concluded that Chinese rice varieties are characterized by a high protein and the grain texture after cooking has high hardness and low stickiness. In a previous study, we developed a novel formula for estimating AAC based on the iodine absorption curve. The validation test showed a determination coefficient of 0.996 for estimating AAC of Chinese rice cultivars as unknown samples. In the present study, we developed a novel formulae for estimating the balance degree of the surface layer of cooked rice (A3/A1: a ratio of workload of stickiness and hardness) based on the iodine absorption curve obtained using milled rice. Abstract : :